Triaxial Centric Churches in Russia of the Classicism period and their European Prototypes - Yakovlev, Alexey N. (Actual Problems of Theory and History of Art, 2015)
Structures with a triangular or triaxial plan existed in Europe as early as in the Middle Ages, but they got extremely widespread in times of Baroque. In Russia first designs of triangular churches appeared in the first half of the 18th century. First triangular churches were built in Moscow in the 1770s. The Church of Our Lady of Vladimir in the estate Vinogradovo (1772–1777) and the Church of St. George in-the-Fields [“na vspol’e”] (1779–1788, has not survived) on the Malaia-Nikitskaya street are associated with V. I. Bazhenov. Neufforge’s project of “The Temple of War” and the projects of triangular churches by L. C. Sturm were prototypes for both buildings. The typology of triaxial centric churches developed in two directions. The 1st line directly used the centric type of triangular buildings, sometimes with emphasizing the corner rotundas. The 2nd line went along the way of combining the centric core of three rotundas and longitudinally oriented refectory [“trapeznaya”] with a bell tower. The main building of this group is the Church of Stt. Cosmas & Damian on Maroseyka street (1790–1803, M. F. Kazakov). In this Assay it is shown how the unusual type of triaxial centric churches became fairly widespread in Russia at the turn of 18th–19th centuries, due to copying popular iconographic models.
Keywords: architecture; Vasilii Bazhenov; Baroque; capital and province; centric building; Classicism; foreign impact; Matvei Kazakov; Jean-François Nuefforge; prototype and copy; rotunda; typology; triangle plan; Leonhard Sturm